Research Progress of MXene-Based Electrode Materials in Aqueous Zinc-Ion Capacitors - Fang, Guian; Lu, Yinqi; Jin, Wanting; Jin, Ji; Zhang, Wenhao; Zhang, Ran (International Journal of Mechanical and Electrical Engineering, 2026)
As a novel energy storage device combining high energy and power density advantages, zinc-ion capacitors demonstrate broad application potential in large-scale energy storage and wearable electronics. MXene, a representative two-dimensional transition metal carbon/nitride, is considered an ideal material for constructing zinc-ion capacitor electrodes due to its excellent conductivity, tunable interlayer spacing, and abundant surface functional groups. This paper systematically reviews the preparation techniques of MXene-based electrodes, performance optimisation strategies and their research progress in zinc-ion capacitors. It first introduces the fundamental properties of MXene materials, focusing on the preparation methods and structural characteristics of pure MXene electrodes, MXene-based binary and multi-component composite electrodes, and flexible MXene electrodes.Subsequently, strategies for optimizing MXene-based electrode performance are explored in depth. Building upon this foundation, practical application advancements of MXene-based electrodes in zinc-ion capacitor energy storage devices are summarized. Finally, potential future research directions are proposed to address the challenges still facing MXene-based electrodes.